Regioselective trans‐Hydrostannation of Boron‐Capped Alkynes - Melot, Romain; Saiegh, Tomas J.; Fürstner, Alois (Chemistry : a European journal, 2021)
Alkynyl‐B(aam) (aam=anthranilamidato) derivatives are readily available bench‐stable compounds that undergo remarkably selective reactions with Bu3SnH in the presence of [Cp*RuCl]4 as the catalyst. The addition follows a stereochemically unorthodox trans‐selective course; in terms of regioselectivity, the Bu3Sn‐ unit is delivered with high fidelity to the C‐atom of the triple bond adjacent to the boracyclic head group (“alpha,trans‐addition”). This outcome is deemed to reflect a hydrogen bonding interaction between the protic −NH groups of the benzo‐1,3,2‐diazaborininone ring system and the polarized [Ru−Cl] bond in the loaded catalyst, which locks the substrate in place in a favorable orientation relative to the incoming reagent. The resulting isomerically (almost) pure gem‐dimetalated building blocks are amenable to numerous downstream functionalizations; most remarkable is the ability to subject the −B(aam) moiety to Suzuki‐Miyaura cross coupling without need for prior hydrolysis while keeping the adjacent Bu3Sn‐ group intact. Alternatively, the tin residue can be engaged in selective tin/halogen exchange without touching the boron substituent; the fact that the two ‐NH entities of −B(aam) do not protonate organozinc reagents and hence do not interfere with Negishi reactions of the alkenyl halides thus formed is another virtue of this so far underutilized boracycle. Overall, the ruthenium catalyzed trans‐hydrostannation of alkynyl‐B(aam) derivatives opens a practical gateway to isomerically pure trisubstituted alkenes of many different substitution patterns by sequential functionalization of the 1‐alkenyl‐1,1‐heterobimetallic adducts primarily formed. Peripheral: A hydrogen‐bonding array in the periphery of the loaded ruthenium catalyst is the likely cause for the excellent regioselectivity observed in the hydrostannation of bench‐stable alkynyl‐B(aam) derivatives (aam=anthranilamido). The reaction follows a stereochemically unorthodox trans‐addition mode and delivers highly versatile gem‐dimetalated alkene building blocks for synthesis.